Pengembangan Multimedia Pembelajaran Matematika Pada Materi Grafik Persamaan Garis Lurus Berbasis Android Menggunakan Aplikasi Scratch - Salamah, Fatihatus; Sudihartinih, Eyus (Journal Mathematics Education Sigma [JMES], 2024)
The purpose of this study was to design learning media in the form of an Android-based online game on straight line equation graphic material using Scratch. This research method uses the Multimedia Development Life Cycle (MDLC) development model with six stages, namely concept, design, collecting, assembly, testing, and distribution. Data was collected by distributing open questionnaires via Google Forms and interviews to find out user responses to the trial programs that had been made. The research participants were 14 students consisting of 3 males and 11 females from a mathematics education study program at a university in Bandung. MDLC stages. The results of the calculation of user responses show that the average percentage of each indicator is 92.5%, the acquisition of positive statements is in the very good category. This there is a need for further research to determine the effectiveness and practicality of using instructional media in the process of learning and developing games on different topics.